ANTIOXIDANT ACTIVITY OF WATER APPLE (Syzygium aqueum) FRUIT ANDFRAGRANT MANGO (Mangifera odorata) FRUIT - Saptarini, Nyi Mekar; Herawati, Irma Erika (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Objective: The aim of this study was to compare the antioxidant activity of fruit of water apple and fragrant mango against 1,1-diphenyl-2- picrylhydrazyl as a free radical. Methods: This study was conducted by visible spectrophotometry. Results: The water apple and fragrant mango contain reducing compounds including vitamin C. The vitamin C content of water apple and fragrant mango fruit was 0.087% (w/w) and 0.050% (w/w), respectively. The inhibitory concentration 50% value of fresh fruit of water apple and fragrant mango was 4.857 Î¼g/ml and 4.379 Î¼g/ml, respectively. Conclusion: Antioxidant activity of water apple fruit was higher than fragrant mango fruit.